STUDI DESKRIPTIF PERSONAL BRANDING MAHASISWA MELALUI MEDIA SOSIAL INSTAGRAM PADA MAHASISWA DI ERA DIGITAL - Alya Haninda Rahmawati, Hana Intan Nuraini, Kaniya Gita Putri M, Septria Indaryani, Zulfa Izzatun Ni (FKIP UMN ALWASHLIYAH, 2026)
This study aims to analyse the use of Instagram as a tool for personal branding among university students, as well as the factors influencing it. The study employs a descriptive quantitative approach with a sample of 77 respondents, determined using the Slovin formula with a margin of error of 10%. Data were collected via an online Likert-scale questionnaire and analysed using descriptive statistics with IBM SPSS Statistics version 25. The results indicate that the majority of respondents demonstrate a high level of awareness in utilising Instagram as a medium for self-presentation, particularly regarding visual aspects and audience understanding. Students have been able to manage their digital identities and build positive perceptions. However, strategic aspects such as content consistency and audience adaptation remain suboptimal. These findings suggest that although Instagram usage is active, personal branding is not yet fully managed strategically. Consequently, the potential for enhancing credibility and competitiveness remains unrealised. Therefore, improved digital literacy encompassing both technical and strategic aspects—is required to ensure personal branding delivers optimal benefits.